DESAIN KEMASAN “TAHU ROBI” DI DESA PURWODADI KECAMATAN TANJUNG BINTANG LAMPUNG SELATAN - Putri Suwarni; Gilar Prambudi (Fakultas Teknik Universitas Tulang Bawang Lampung, 2020)
The attractiveness of a package can not be separated from the target market for which the package is intended. Packaging not only carries the identity of a product, but furthermore, it reflects the image of the producer in supporting consumer satisfaction. Packaging is also an important factor when a product is about to move targets or raise segments from the lower middle segment to the upper middle segment. The packaging design activities carried out by the tofu factory are the shape, material, color, symbol / brand / logo, picture / illustration, and drawing language, the layout has the aim to introduce tofu products to the public and increase purchases. The purpose of this research is to develop a different form of packaging with other forms of tofu packaging. The results of the new packaging design can be found several differences from the old packaging in terms of: a more attractive form of packaging, a packaging model with a size of 250 grams, there is a new logo that has features, illustrations and visualization designed more attractive by displaying the name of the business owner. Keywords : Design, Packaging, Consumer, Logo, Attractive